Recurrent Aortic Dissection in a Patient With an Actin Mutation Treated With a Laser-Fenestrated Aortic Arch Stent-Graft. (August 2018) - Cullen, J. Michael; Ailawadi, Gorav; Angle, John F.; Thomas, Matthew; Upchurch, Gilbert R.
A 58-year-old African American female, who had previously undergone a valve-sparing aortic root replacement for a type A dissection, represented 2 months later with a new focal dissection and aneurysm with intramural hematoma just distal to the origin of the left subclavian artery. Since no landing zone distal to the subclavian artery existed, the patient underwent thoracic endovascular aortic repair with laser fenestration-aided stent-graft placement in the left subclavian artery. The patient recovered without complication, and 52 months later, she is doing well with normal renal function and ambulatory status.